(untitled) (Scientific journal of the Fergana State University, 2026)
The article analyzes the historical development of the concept of beauty in Eastern and Western philosophical thought. Based on the ideas of ancient thinkers such as Socrates, Plato, and Aristotle, the principles of beauty as morality, metaphysical idea, order, and proportion are revealed. Through a comparative analysis with Eastern aesthetic thought, the views of Yassawi, Farabi, Ibn Sina, and Navoi are examined, highlighting the paradigmatic transformation of the concept of beauty. The findings demonstrate that beauty is interpreted not only as an aesthetic category but also as a universal concept closely connected with moral, religious, and spiritual values.